Factors for Increasing Competitive Advantage in MSMEs Reviewed from a Systematic Literature Review - Oktaria, Eka Travilta; Raras, Pungky Nanda; Alam, Iskandar Ali; Barusman, Andala Rama Putra; Habiburrahman, Habiburrahman (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to determine the factors related to competitive advantage, especially in Micro, Small and Medium Enterprises (MSMEs), and to gain an in-depth understanding of the field of Competitive Advantage by classifying, defining, and analyzing the latest scientific literature. Research Methodology: This research uses the systematic mapping study (SMS) method to examine scientific publications on the field of competitive advantage published from time to time based on focus and type of research. Results: The results of this study also provide a summary of current research topics and trends related to Competitive Advantage. Micro, Small and Medium Enterprises (MSMEs) can gain a Competitive Advantage through planned strategies. The goal of this strategy is to generate greater profits than competitors. To gain Competitive Advantage, many factors are equally important. Some of these are challenges, artificial intelligence, adoption, industry, covid, application, technology, data, performance, green innovation, capability, role, supply chain, innovation, and image classification factors. This factor creates and maintains a competitive advantage over competitors. Limitation: Limited number of variables in determining factors related to the development of micro, small, and medium enterprise (MSME) governance, such as MSME performance, Market Orientation, Innovation, Marketing, Dynamic Capabilities. Contribution: This research provides a practical way to learn which topics are appropriate for research and which areas require additional research and help researchers plan future discovery gap (gap) research.